The State Of Takaful Al-Ijtimai’ During Covid-19 In Malaysia:A Review - Junaidah Abu Seman; Hisham Sabri; Wan Nur Fazni Wan Mohamad Nazarie; Nur Adilah Othman (Universiti Sains Islam Malaysia, 2024)
Risk is present in every aspect of human life. Labelled as a black swan event and equated to the economic scene of World War Two, the deadly infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), called coronavirus disease 2019 (COVID-19), signifies a grave risk to public health. As far as the COVID-19 is concerned, people striving to spread risk from one party to another, seeking assistance which is not limited to the financial aspect. In the case of the COVID-19 pandemic relief mission, the concept and practices of takaful al-ijtimai’ is more applicable as it’s meaning and scopes are broader; covers both financial and non-financial assistance and not limited under the purview of the country’s laws. Using secondary data, this study aims to explore the concept and scopes of social security or takaful al-ijtimai’ from an Islamic point of view and present the current state of the art in the implementation of takaful al-ijtimai’ during the COVID19 pandemic in Malaysia. It is hoped that the review would be useful for understanding and promoting the concept of takaful al-ijtimai’ as one important tool to achieve sustainable development goals.